Advances in the Study of Structural Modification and Biological Activities of Anoplin - Wu, Ye; Huang, Rui; Jin, Jin-Mei; Zhang, Li-Jun; Zhang, Hong; Chen, Hong-Zhuan; Chen, Li-Li; Luan, Xin (Frontiers in Chemistry, 2020)
Anoplin is an amphipathic, α-helical bioactive peptide from wasp venom. In recent years, pharmaceutical and organic chemists discovered that anoplin and its derivatives showed multiple pharmacological activities in anti-bacterial, anti-tumor, anti-fungal and anti-malarial. Due to the simple and unique structure and diverse biological activities, anoplin has attracted considerable research interests. This review highlights the advances in structural modification, biological activities and the outlook of anoplin in order to provide basis for new drug design and delivery.